2017
DOI: 10.1111/pedi.12556
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to a pediatric diabetic ketoacidosis protocol in children presenting to a tertiary care hospital

Abstract: Health care providers' adherence to the BCCH DKA protocol is poor. More severe dehydration at presentation is associated with longer duration of insulin infusion. Further knowledge translation initiatives focused on accurate estimation of volume depletion to ensure appropriate initial fluid resuscitation-as well as careful monitoring during DKA hospitalization-are important, especially in community centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The management of DKA in any setting, both for patients with newly or previously diagnosed T1DM, can be divided into four physiologic principles which are restoration of fluid volume, inhibition of lipolysis, correction of electrolyte abnormalities and correction of acidosis. Delayed, insufficient or inappropriate treatment is a potential risk for developing complications of DKA (22). The timing of fluid therapy as an initial treatment has a considerable effect on the outcome of DKA and it is recommended that it should be given within the first hour (23).…”
Section: Discussionmentioning
confidence: 99%
“…The management of DKA in any setting, both for patients with newly or previously diagnosed T1DM, can be divided into four physiologic principles which are restoration of fluid volume, inhibition of lipolysis, correction of electrolyte abnormalities and correction of acidosis. Delayed, insufficient or inappropriate treatment is a potential risk for developing complications of DKA (22). The timing of fluid therapy as an initial treatment has a considerable effect on the outcome of DKA and it is recommended that it should be given within the first hour (23).…”
Section: Discussionmentioning
confidence: 99%
“…Even with local protocols in place, studies have shown that interpretation of such protocols may vary, and adherence is still imperfect. 1,15,16 Using the TEM, we were able to identify factors that may contribute to nonadherence. In terms of threats, cases where it was a first-time presentation of T1DM or where the initial assessment was done by a learner (either medical student or resident), were less likely to have the order set filled out from the beginning.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding is in agreement with previous studies that have highlighted the differences in acute DKA management both between different hospitals and among physicians within a given center. Even with local protocols in place, studies have shown that interpretation of such protocols may vary, and adherence is still imperfect 1,15,16 …”
Section: Discussionmentioning
confidence: 99%
“…Several RCTs have been conducted in children with DKA. As a result, the most effective and safest fluid and infusion scheme to manage DKA in children remains unknown 12–14 . Therefore, through a systematic review and network meta‐analysis (NMA), this work sought to determine the comparative effectiveness—in terms of neurological deterioration and metabolic control—of the fluid schemes used to rehydrate children with DKA.…”
Section: Introductionmentioning
confidence: 99%